2012
DOI: 10.1523/jneurosci.5543-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic But Not Postsynaptic GABA Signaling at Unitary Mossy Fiber Synapses

Abstract: Dentate gyrus granule cells have been suggested to corelease GABA and glutamate both in juvenile animals and under pathological conditions in adults. Although mossy fiber terminals (MFTs) are known to express glutamic acid decarboxylase (GAD) in early postnatal development, the functional role of GABA synthesis in MFTs remains controversial, and direct evidence for synaptic GABA release from MFTs is missing. Here, using GAD67-GFP transgenic mice, we show that GAD67 is expressed only in a population of immature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 36 publications
(61 reference statements)
7
46
0
Order By: Relevance
“…39 Immature granule neurons in the postnatal DG express functional GABA B receptors that modulate presynaptic excitability and could potentially influence differentiation of these cells. 16 Interestingly, even though dendritic length and morphology of newborn neurons were not analyzed, a decrease in Doublecortin expression and an increase in NeuN expression were detected in the DG of adult GABA B1deficient mice, suggesting that accelerated neuronal maturation, in addition to increased cell proliferation, contributes to enhanced hippocampal neurogenesis in the absence of functional GABA B receptors. 40 However, and in apparent contrast to these findings, treatment with a GABA B receptor antagonist had no significant effects on dendritic initiation in postnatally generated olfactory bulb interneurons.…”
Section: Contribution Of Gaba B Receptor Signaling To the Regulation mentioning
confidence: 95%
See 3 more Smart Citations
“…39 Immature granule neurons in the postnatal DG express functional GABA B receptors that modulate presynaptic excitability and could potentially influence differentiation of these cells. 16 Interestingly, even though dendritic length and morphology of newborn neurons were not analyzed, a decrease in Doublecortin expression and an increase in NeuN expression were detected in the DG of adult GABA B1deficient mice, suggesting that accelerated neuronal maturation, in addition to increased cell proliferation, contributes to enhanced hippocampal neurogenesis in the absence of functional GABA B receptors. 40 However, and in apparent contrast to these findings, treatment with a GABA B receptor antagonist had no significant effects on dendritic initiation in postnatally generated olfactory bulb interneurons.…”
Section: Contribution Of Gaba B Receptor Signaling To the Regulation mentioning
confidence: 95%
“…16,40 Expression of GABA B receptors in the adult SVZ has not been addressed in great detail. However, mRNA of several G-protein-coupled receptors, including the GABA B1 receptor subunit, has been detected in SVZ NSCs.…”
Section: Contribution Of Gaba B Receptor Signaling To the Regulation mentioning
confidence: 99%
See 2 more Smart Citations
“…The intrinsic and synaptic properties of immature GCs in another line of GAD67-GFP mice have also been well characterized (Cabezas et al 2013). Although the functional role of GABA synthesis in immature GCs remains controversial (Uchigashima et al 2007), recent work using GAD67-GFP transgenic mice showed that GABA release from immature mossy fibers can modulate mossy fiber excitability via GABA B autoreceptors (Cabezas et al 2012). …”
Section: Gad67 Reporter Micementioning
confidence: 99%